The New Seismotectonic Atlas of Greece (v1.0) and Its Implementation - Ioannis Kassaras; Vasilis Kapetanidis; Athanassios Ganas; Tzanis, Andreas; Kosma, Chrysanthi; Andreas Karakonstantis; Sotirios Valkaniotis; Chailas, Stylianos; Kouskouna, Vasiliki; Panayotis Papadimitriou (Geosciences, 2020)
Knowledge and visualization of the present-day relationship between earthquakes, active tectonics and crustal deformation is a key to understanding geodynamic processes, and is also essential for risk mitigation and the management of geo-reservoirs for energy and waste. The study of the complexity of the Greek tectonics has been the subject of intense efforts of our working group, employing multidisciplinary methodologies that include detailed geological mapping, geophysical and seismological data processing using innovative methods and geodetic data processing, involved in surveying at various scales. The data and results from these studies are merged with existing or updated datasets to compose the new Seismotectonic Atlas of Greece. The main objective of the Atlas is to harmonize and integrate the most recent seismological, geological, tectonic, geophysical and geodetic data in an interactive, online GIS environment. To demonstrate the wealth of information available in the end product, herein, we present thematic layers of important seismotectonic and geophysical content, which facilitates the comprehensive visualization and first order insight into seismic and other risks of the Greek territories. The future prospect of the Atlas is the incorporation of tools and algorithms for joint analysis and appraisal of these datasets, so as to enable rapid seismotectonic analysis and scenario-based seismic risk assessment.
Keywords: crustal deformation; GIS mapping; Seismotectonics